Persistent Idiopathic Facial Pain Associated with Somatoform Disorder in an 11-Year-Old Boy - Yoshihiko Sakurai; Asami Fujii; Fumie Kato (Case Reports in Psychiatry)
Persistent idiopathic facial pain (PIFP) is a poorly understood chronic disorder that rarely occurs in children. An 11-year-old boy initially presented with right cheek pain and a streptococcal infection 6 weeks previously. Facial cellulitis was suspected, which was resolved by antibiotic treatment. The right cheek pain recurred within 4 weeks of this initial visit. Because the antibiotic treatment did not relieve the pain, the patient visited our outpatient clinic. Physical examination revealed facial tenderness in an area that corresponded with the region supplied by the second branch of the trigeminal nerve (maxillary nerve), suggesting trigeminal neuralgia (TN). However, brain magnetic resonance imaging revealed no vascular compression. Furthermore, the continuous nagging and dull nature of the pain experienced by the patient differed from the sudden and severe nature of pain associated with TN. Subsequently, PIFP was diagnosed. The patient was unable to attend school because of prolonged lassitude, nausea, headache, and anorexia. Psychological counseling revealed psychological stress related to his out-of-school life. Upon learning stress management through psychotherapy, his general malaise gradually improved, and he was able to attend school with more facial expressions. This case indicates the psychogenic aspect of PIFP as well as the value of psychological counseling.